Effect of Al content on hot tearing behaviour of Mg–xAl–2Ca–2Sm alloys. Issue 1 (2nd January 2019) - Chen, Yanhong; Wang, Liping; Feng, Yicheng; Wang, Lei; Guo, Erjun
ABSTRACT: Mg– x Al–2Ca–2Sm ( x  = 3, 5, 9 and 15) alloys were tested using an 'L'-shaped sand mould serving as a hot tearing testing system. The experimental results showed that the solidification range of the Mg– x Al–2Ca–2Sm alloys first decreased and then increased as the Al content was increased. Furthermore, by increasing the Al content, the dendritic arms of the α-Mg phase become more developed, and the hot tearing tendency of the Mg– x Al–2Ca–2Sm alloys increased. In addition, the variety of precipitated phases was seen to be affected by the Al content and the tendency for hot tearing depended on the precipitated phase. The tendency of the Mg– x Al–2Ca–2Sm alloys for hot tearing first decreased and then increased with increasing Al content.